Determinant of Formal Entrepreneurship and Entrepreneur Transition During Covid-19 Pandemic - Tasmilah (East Java Economic Journal, 2021)
Entrepreneurship in East Java is dominated by informal entrepreneurs. To increase productivity and absorption of formal workers, a transition from informal entrepreneurs to formal entrepreneurs is needed. Using Sakernas August 2020 data, this study aims to analyze the determinants of formal entrepreneurship in East Java. In addition, using Sakernas panel data in August 2019 and 2020, we investigate the entrepreneurial transition in one year. The results of the binomial logistic regression show that male gender, higher education level, entrepreneurial skills, and use of digital technology such as the internet have a greater tendency to become formal entrepreneurs in East Java. Similarly, formal entrepreneurs who use the digital technology have less chance of turning into informal entrepreneurs during the Covid-19 pandemic.